Singing rhyming verse: the rhyme in Joaquín Sabina’s lyrics - Soto Zaragoza, Javier (Anuario de Estudios Filológicos, 2024)
Despite being an essential part of his lyrics, to this date no attention had yet been paid to the rhyme in Joaquín Sabina’s song book, one of the most important in Spanish literature and music in the late 20th century and the early 21st century. This study constitutes a first approach to that part of the Andalusian singer-songwriter’s literary practice and analyzes various uses of the rhyme in his lyrics to distinguish the most common models, the reasons behind its use and its literary quality.